2017
DOI: 10.1021/acs.jpcb.7b02899
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Conformation-Dependent Preferential Binding of Ethanol to Cationic Glycylalanylglycine in Water/Ethanol by Vibrational and NMR Spectroscopy

Abstract: The conformational propensity of amino acid residues is determined by an intricate balance of peptide-solvent and solvent-solvent interactions. To explore how the systematic replacement of water by a cosolvent affects the solvation of both the amino acid backbone and side chains, we performed a combined vibrational spectroscopy and NMR study of cationic glycylalanylglycine (GAG) in different ethanol/water mixtures of between 0 and 42 mol percent ethanol. Classical model peptide N'-methylacetamide was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(42 citation statements)
references
References 100 publications
5
37
0
Order By: Relevance
“…The environment of the amide group can be experimentally probed by chemical shift measurements. Previously reported values for GAG [72,73] (Table S8) are consistent with an increased hydration of the amide group of residue 2 relative to residue 3 (Table S6, columns 3 and 4) as increased hydration produces upfield shift of the chemical shift [74]. The carbonyl oxygen of residue 1 forms significantly fewer HBs with water than carbonyl oxygens of residues 2 and 3 ( Table S7).…”
Section: The Ppii State Enables Glycine and Alanine Residues To Form supporting
confidence: 78%
See 1 more Smart Citation
“…The environment of the amide group can be experimentally probed by chemical shift measurements. Previously reported values for GAG [72,73] (Table S8) are consistent with an increased hydration of the amide group of residue 2 relative to residue 3 (Table S6, columns 3 and 4) as increased hydration produces upfield shift of the chemical shift [74]. The carbonyl oxygen of residue 1 forms significantly fewer HBs with water than carbonyl oxygens of residues 2 and 3 ( Table S7).…”
Section: The Ppii State Enables Glycine and Alanine Residues To Form supporting
confidence: 78%
“…Although there is no experimental data on conformational ensemble of central glycine in GGG, Eker et al reported that, while alanine-based tripeptides favor pPII in water, their pPII content is significantly reduced in DMSO [75]. Consistent with the key role of water in pPII stabilization, the addition of ethanol to water was also shown to disfavor the pPII mesostate of guest alanine in cationic GAG [72,76].…”
Section: Dmso Reduces Ppii Content Of the Central Glycine In Gggmentioning
confidence: 99%
“…NMR experiments probing chemical shifts of amide protons are indicators of the groups involvement with water and CO groups 63 , 69 , 70 . While beyond the scope of the present study, Hetero-Nuclear-Correlation-Spectroscopy (HSQC) experiments 71 probing the temperature dependence of J coupling on isotopically labeled polymers could provide additional information on the involvement of amide protons 72 , 73 in hydrogen bonding.…”
Section: Resultsmentioning
confidence: 99%
“…However, several peptides without aromaticity have been shown to readily self‐assemble into fibril networks. For example, glycine‐alanine‐glycine (GAG) and glycine‐histidine‐glycine (GHG) self‐assemble into very long microfibrils under the right conditions 19–26 . More specifically, GAG forms fibrils in the presence of a critical fraction of ethanol that depends on peptide concentration 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Recent experimental studies suggest the hypothesis that GAG's self‐assembly is initiated by the accumulation of GAG at the ethanol/water interface, with the protonated C‐terminal immersed in ethanol and the N‐terminal exposed to water 19 . The amide I′ region of the GAG fibrils exhibits a doublet with rather sharp bands at 1644 and 1670 cm −1 , which means that GAG does not self‐assemble into typical β‐sheet tapes or ribbons 19 . Note that β‐sheets are generally considered the fundamental building block of amyloid‐like fibrils 27,28 .…”
Section: Introductionmentioning
confidence: 99%